Effective Use of Land Resources in Agriculture - B. F. Sultonov; M. T. (International Journal on Economics, Finance and Sustainable Development, 2021)
Increasing the economic efficiency of the use of land resources is the main element that has a decisive impact on the result of social production. But salinization, erosion and desertification lead to serious land degradation, which, in turn worsens human health and ecosystem services. The article develops land relations in the agricultural sector, you will analyze the factors that limit the efficiency of the use of agricultural land.